2009
DOI: 10.1037/a0015952
|View full text |Cite
|
Sign up to set email alerts
|

Happiness unpacked: Positive emotions increase life satisfaction by building resilience.

Abstract: Happiness – a composite of life satisfaction, coping resources, and positive emotions – predicts desirable life outcomes in many domains. The broaden-and-build theory suggests that this is because positive emotions help people build lasting resources. To test this hypothesis we measured emotions daily for one month in a sample of students (N=86) and assessed life satisfaction and trait resilience at the beginning and end of the month. Positive emotions predicted increases in both resilience and life satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

68
719
5
41

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,165 publications
(833 citation statements)
references
References 48 publications
68
719
5
41
Order By: Relevance
“…This increased cognitive flexibility is believed to lead to new ways of problem solving that build resilience. It was suggested that because positive emotions can increase resilience, positive emotions allow persons to develop resources that help them deal with life challenges that in turn lead to life satisfaction (Cohn, Fredrickson, Brown, Mikels, & Conway, 2009). Research supports the claim that psychological resilience is associated with positive emotions especially during stressful times (e.g., Ong, Bergeman, Bisconti, & Wallace, 2006).…”
supporting
confidence: 48%
“…This increased cognitive flexibility is believed to lead to new ways of problem solving that build resilience. It was suggested that because positive emotions can increase resilience, positive emotions allow persons to develop resources that help them deal with life challenges that in turn lead to life satisfaction (Cohn, Fredrickson, Brown, Mikels, & Conway, 2009). Research supports the claim that psychological resilience is associated with positive emotions especially during stressful times (e.g., Ong, Bergeman, Bisconti, & Wallace, 2006).…”
supporting
confidence: 48%
“…For example, in one study, daily positive emotions predicted increases in life satisfaction and resilience over the course of a month (Cohn et al, 2009). In another investigation, the experience of more positive emotions and fewer negative emotions explained the association between resilience and life satisfaction (Liu et al, 2013).…”
Section: Mechanisms Of Change: the Role Of Positive And Negative Emotmentioning
confidence: 97%
“…Johnson, Penn, Fredrickson, Meyer, Kring, a Brantley (2009) ve své studii poukazují, jak mohou pozitivní emoce (kam patří veselí, jehož tělesnou reakcí je smích) přerušit emoce negativní. Navíc pozitivní emoce pomáhají lepšímu vnímá-ní skutečnosti (viz také Nešpor, 2011) a napomáhají zvyšovat životní spokojenost a odolnost psychickou (Cohn, Fredrickson, Brown, Mikels, & Conway, 2009).…”
Section: Oblast Psychickáunclassified
“…Navíc studie prokázaly, že smích (jak spontánní tak simulovaný) vede k veselosti a celkové dobré náladě, a tím pomáhá čelit vyčerpanosti, pře devším psychické (viz např. Cohn, Fredrickson, Brown, Mikels, & Conway, 2009;Johnson, 2009;Nešpor, 2010a;Vagnoli, Caprilli, & Messeri, 2010 Smích působí zvláště na psychickou zdatnost člověka např. jako významný prostředek regulace stresu.…”
unclassified